Boundary of Istimta' For Husband Against Menstruating Wife (Comparative Study of Imam Malik and Imam As Syafi'i) - Hakim, Pahmi; Efendi, Rahmad (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This research examines the "Istimta' Limits' For Husbands Toward Wife Who Has Menstruation. In more detail, it discusses ISTIMTA'. is a law that is prescribed for a couple so that there is no more opportunity for the husband to commit adultery even though the wife is menstruating, therefore there is a limit of istimta' for the husband towards the wife who is menstruating so that it is more build good family relationships.Opportunities for adultery for husbands are very few because the majority of scholars allow istimta' but differ in opinion as to what istimta' (having fun) with a menstruating wife can be chosen by the husband taking into account the procedures and procedures in accordance with Islamic law. There are several laws that the scholars are not united and have different opinions, in particular regarding the concept of istimta limits.This research is about to examine the opinion of two madhhab priests, namely Imam as Syafi'i and Imam Al Maliki.The problem being investigated is how the views of imam as Syafi'i and imam maliki on the concept of istimta' law on menstruating women. This study aims to analyze the views of two priests of the madhhab, namely Imam As Syafi'i and Imam Al Maliki regarding the limit of istimta' for husbands towards wives who are menstruating. This research is research that uses a normative approach with a qualitative descriptive method, ie describes the views of two madhhab priests, namely imam as Syafi'i and imam Al Maliki. Research results obtained from the discussion of this study, namely that if a wife is menstruating there is a limit for the husband to be istimta' with said wife, so when a husband ignores the istimta' limits for a husband towards a wife who is menstruating which is permissible then the law is haram. So it is important to explain in this related thesis.